2017
DOI: 10.1159/000485399
|View full text |Cite
|
Sign up to set email alerts
|

Novel Functional Role of Heat Shock Protein 90 in Mitochondrial Connexin 43-Mediated Hypoxic Postconditioning

Abstract: Background/Aims: Previous studies have shown that heat shock protein 90 (HSP90)-mediated mitochondrial import of connexin 43 (Cx43) is critical in preconditioning cardioprotection. The present study was designed to test whether postconditioning has the same effect as preconditioning in promoting Cx43 translocation to mitochondria and whether mitochondrial HSP90 modulates this effect. Methods: Cellular models of hypoxic postconditioning (HPC) from rat heart-derived H9c2 cells and neonatal rat cardiomyocytes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…Finally, our results also confirm previous works demonstrating that, as occurred with the antiarrhythmic effect of IPoC during reperfusion, Cx43 is not involved in protection against infarction induced by the maneuver [49]. However, others have suggested that mitochondrial Cx43 might play a role in hypoxic postconditioning against infarction in H9c2 cells and neonatal rat cardiomyocytes [50]. These discrepancies deserve further research in the future.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, our results also confirm previous works demonstrating that, as occurred with the antiarrhythmic effect of IPoC during reperfusion, Cx43 is not involved in protection against infarction induced by the maneuver [49]. However, others have suggested that mitochondrial Cx43 might play a role in hypoxic postconditioning against infarction in H9c2 cells and neonatal rat cardiomyocytes [50]. These discrepancies deserve further research in the future.…”
Section: Discussionsupporting
confidence: 90%
“…Reinforcing the idea that HSPs are important in tissue resilience generally, they are reported to be effective in slowing muscular dystrophy in a rat model, 368,369 in slowing the development of cortical pathology in a rodent model of dementia, 370,371 in mitigating the tissue pathologies of diabetes, 372 in protecting the failing heart, 373 in reducing neuroinflammatory markers in astrocytes, and in conditioning of cardiomyocytes 374 and fibroblasts 375 in vitro. In short, HSPs are upregulated by a range of stresses and are protective to a range of tissues, ranges comparable those of the inducers of resilience and of tissues protected, considered in previous sections.…”
Section: Heatmentioning
confidence: 75%
“…For this purpose, H9c2 cells were treated with 1 µ M Doxo for 3 and 6 h, in both the absence and presence of radicicol, an Hsp90 inhibitor. Indeed, although it is well known that Hsp90 is involved in a number of other cellular processes ( 22 ), radicicol is widely used as a pharmacological tool to block the Doxo-induced translocation of Cx43 to the mitochondria ( 4 , 9 ), just as another Hsp90 inhibitor has been used to study the role of mitochondrial Cx43 in cardioprotection ( 35 ).…”
Section: Discussionmentioning
confidence: 99%